Gender regimes in Slovenian academic field - Smrdelj, Rok (Annales. Series historia et sociologia, 2024)
Sexual harassment and other forms of sexual violence are widespread social phenomena, and thus also present in academic field. To examine how the gender regimes of Slovenian academic institutions are reflected in their internal regulations regarding sexual harassment and other forms of sexual violence, we analyse them in this paper. We find that public higher education institutions, notably the University of Ljubljana and its Faculty of Arts, regulate this area more comprehensively than private higher education institutions and public research institutes. In general, our analysis reveals that while some Slovenian academic institutions maintain a male-dominated gender regime, others actively work to deconstruct it.
Keywords: akademsko polje; analiza vsebine; interni akti; Slovenija; spolni režimi; spolno nadlegovanje; spolno nasilje